Frankie Foster pick 'n' mix - Ure, Jean (HarperCollins London, 2011)
"When Frankie's mum agrees to have a friend's daughter to stay for a fortnight, it falls on Frankie's shoulders to look after Emilia. Having another girl share her broom cupboard of a bedroom is one thing, but wherever Emilia goes, trouble seems to follow, however hard Frankie tries to keep her out of it!"--Publisher's website. Suggested level: primary, intermediate